Art Moscow 2000 : 4th International Art Fair. - Shvetsova, L.; Shvidkoy, M.E. (Moscow : Art Moscow Foundation, 2000)
Lowe, Rachel ; Langlands & Bell ; Kulik, Oleg ; Pavin, Mikhail ; Angelov, Nicolai ; Ponomarev, S. ; Brodsky, Alexander ; Florensky, Olga & Alexander ; Koshlyakov, Valery ; Abaza, Aleksandr ; Hornsleth, Kristian ; Mapplethorpe, Robert ; Cragg, Tony (Anthony) ; Matisse, Henri ; Belsky, Boris ; Bonin, Cosima von ; Althoff, Kai ; Konstantinov, Alexander ; Apandi, Magomedov ; Khalfin, Rustam ; Tikhonova, Juliya ; Tsibakhashvili, Guram ; The Tchetvertaya Vysota Group ; Saudek, Jan
Engels & Russisch
Art Moscow 2000, Central House of Artist, Moscow, May 16 - 21, 2000
boek
Keywords: Moskou